Crafting branded entertainment: insights from short films awarded at Cannes Lions - Rodríguez-Rabadán Benito, María; Sidorenko, Pavel; Abellán, Maria (Frontiers in Communication, 2025)
Branded entertainment represents communication assets rooted in entertainment such as short films, among others, in which a brand creates original and entertainment content based on value creation, engagement, relevance, and non-intrusiveness and paid wholly or in part by a brand. This study examines the creative process behind brand short films, specifically those awarded at the Cannes Lions 2023. Through interviews with international experts and qualitative case analysis, it identifies fundamental patterns and key factors for the success of these productions. The study proposes an applicable model based on three dimensions: production, content, and audience. These dimensions encompass the creative and strategic quality of the works as well as their capacity to generate engagement and brand recall. The findings highlight the importance of interdisciplinary collaboration between creatives and brands, where storytelling and brand values are organically integrated, prioritizing entertainment over direct brand or product promotion. Experts emphasize the need for high- quality content aligned with the standards of the entertainment industry. This work contributes to the theoretical and practical development of branded entertainment, specifically in the form of brand films, offering a framework for crafting narratives that not only reflect brand values but also position themselves as significant and diverse cultural assets within the digital economy.